Protective effect of dietary phosphorus intake on cardiovascular mortality in asthma: evidence from NHANES 1999–2018 - Yang, Shuwen; Chen, Haiyan; Xie, Congyi; Zhang, Ning (Frontiers in Nutrition, 2025)
BackgroundAsthma is associated with an increased risk of cardiovascular mortality, potentially influenced by dietary phosphorus intake through its effects on inflammation and oxidative stress.MethodsData from 7,539 asthma patients in the National Health and Nutrition Examination Survey (NHANES) 1999–2018 cohort were analyzed using weighted Cox proportional hazards models to estimate hazard ratios (HR) and 95% confidence intervals (CI). Kaplan-Meier survival curves and a nomogram were used to assess survival probabilities and individualized risk, while restricted cubic spline (RCS) analysis evaluated non-linear dose-response relationships. Sensitivity analyses were conducted to test the robustness of the findings.ResultsHigher dietary phosphorus intake was associated with reduced cardiovascular mortality (HR: 0.43; 95% CI: 0.22–0.85 for the highest vs. lowest quartile; p for trend = 0.018). Kaplan-Meier curves showed improved survival with increasing phosphorus intake, a result consistently supported by subgroup analyses. RCS analysis confirmed a non-linear dose-response relationship, identifying a threshold at 1,861.52 mg/day, below which higher phosphorus intake was significantly associated with lower cardiovascular mortality. However, above this threshold, the protective effect diminished. Sensitivity analyses further validated these results.ConclusionElevated dietary phosphorus intake is associated with reduced cardiovascular mortality in asthma patients, suggesting its potential as a dietary intervention.